Effects of praziquantel and artesunate on the tegument of adult Schistosoma mekongi harboured in mice - Wannee Jiraungkoorskul (2018)
The effects of praziquantel and artesunate on the tegument of adult Schistosoma mekongi harboured in mice were compared using scanning electron microscopy (SEM). Forty-two mice infected with S. mekongi for 49 days were treated intragastrically with either 300 mg/kg praziquantel or 300 mg/kg artesunate. Mice were sacrificed 1 or 3 days post-treatment. Worms were collected by perfusion and examined by SEM. One to 3 days after administration of artesunate, the tegument of S. mekongi showed severe swelling, vacuolization, fusion of the tegumental ridges and loss or shortening of the spines on the trabeculae, collapse and peeling. Praziquantel induced similar tegumental alterations as those observed after administration of artesunate, but they were less severe. Three days post-treatment, there was evidence of recovery only in the case of praziquantel. The results of our study suggest that artesunate is more effective than praziquantel in causing tegumental damage in adult S. mekongi, and provides a basis for subsequent clinical trials. © 2005 Elsevier Ireland Ltd. All rights reserved.